Toksikologi dan efek farmakologi senyawa flavonoid dalam tumbuhan obat - Ardiansyah, Fahrus Surya (Maliki Interdisciplinary Journal, 2025)
Flavonoids are a group of polyphenolic compounds that are widely found in medicinal plants and have various pharmacological activities, including as antioxidants, anti-inflammatory, and anticancer. These compounds have been used in various medical and pharmaceutical applications, both in the form of supplements and herbal therapies. However, behind their benefits, flavonoids also have toxic potential that needs to be considered. Several studies have shown that consumption of flavonoids in high doses can cause hepatotoxicity, nephrotoxicity, and impaired drug metabolism through the inhibition of cytochrome P450 enzymes. In addition, some flavonoids have cytotoxic effects on healthy cells and are potentially mutagenic under certain conditions. This review aims to review the toxicological aspects and pharmacological effects of flavonoids based on recent studies. The method used in this study is literature analysis from various relevant scientific journals. The review results show that although flavonoids have many health benefits, their use needs to be closely monitored to prevent adverse side effects. Therefore, stricter regulation, dosage control, and further research on flavonoid safety are needed to ensure their safe and effective use in the medical world.